Identification of an Efflux Transporter LmrB Regulating Stress Response and Extracellular Polysaccharide Synthesis in Streptococcus mutans - Liu, Jia; Guo, Lihong; Liu, Jianwei; Zhang, Jianying; Zeng, Huihui; Ning, Yang; Wei, Xi (Frontiers in Microbiology, 2017)
Efflux transporters have been implicated in regulating bacterial virulence properties such as resistance to antibiotics, biofilm formation and colonization. The pathogenicity of Streptococcus mutans, the primary etiologic agent of human dental caries, relies on the bacterium’s ability to form biofilms on tooth surface. However, the studies on efflux transporters in S. mutans are scare and the function of these transporters remained to be clarified. In this study, we identified an efflux transporter (LmrB) in S. mutans through cloning the lmrB gene into Escherichia coli. Introducing lmrB into E. coli conferred a multidrug-resistant phenotype and resulted in higher EtBr efflux activity which could be suppressed by efflux inhibitor. To explore whether LmrB was involved in S. mutans virulence properties regulation, we constructed the lmrB inactivation mutant and examined the phenotypes of the mutant. It was found that LmrB deficiency resulted in increased IPS storage and prolonged acid production. Enhanced biofilm formation characterized by increased extracellular polysaccharides (EPS) production and elevated resistance to hydrogen peroxide and antimicrobials were also observed in lmrB mutant. To gain a better understanding of the global role of LmrB, a transcriptome analysis was performed using lmrB mutant strain. The expression of 107 genes was up- or down-regulated in the lmrB mutant compared with the wild type. Notably, expression of genes in several genomic islands was differentially modulated, such as stress-related GroELS and scnRK, sugar metabolism associated glg operons and msmREFGK transporter. The results presented here indicate that LmrB plays a vital global role in the regulation of several important virulence properties in S. mutans..